Impact of selective anti‐BMP9 treatment on tumor cells and tumor angiogenesis. Issue 10 (20th October 2016) - Brand, Verena; Lehmann, Christian; Umkehrer, Christian; Bissinger, Stefan; Thier, Martina; de Wouters, Mariana; Raemsch, Romi; Jucknischke, Ute; Haas, Alexander; Breuer, Sebastian; Birzele, Fabian; Racek, Tomas; et al.
Abstract: The role of bone morphogenic protein 9 (BMP9) signaling in angiogenesis has been controversial, with a number of studies showing that it acts either as a pro‐angiogenic or, conversely, as an anti‐angiogenic factor in a context‐dependent manner. Notably, BMP9 was also reported to function in both pro‐ or anti‐tumorigenic roles during tumor progression. It has therefore remained unclear, whether selective BMP9 inhibition is a useful target for antibody therapy of cancer. To shed light on these questions, we characterized BMP9 expression in plasma of patients with different cancer indications and found elevated levels of pro‐domains and precursor BMP9 with a strong response in renal cell carcinoma (RCC). These studies prompted us to evaluate the potential of selective anti‐BMP9 cancer therapy in RCC. We generated a novel monoclonal therapeutic antibody candidate, mAb BMP9‐0093, that selectively targets all different BMP9 variants but does not bind to the closest homolog BMP10. In vitro, mAb BMP9‐0093 treatment inhibited signaling, endothelin‐1 (ET‐1) production and spreading of endothelial cells and restored BMP9‐induced decrease in pericyte migration and attachment. Furthermore, BMP9‐mediated epithelial–mesenchymal transition of renal cell carcinoma cells was reversed by mAb BMP9‐0093 treatment in vitro. In vivo, mAb BMP9‐0093 showed significant anti‐tumor activity that was associated with an increase in apoptosis as well as a decrease in tumor cell proliferation and ET‐1 release. Furthermore, mAb BMP9‐0093 induced mural cell coverage of endothelial cells, which was corroborated by a reduction in vascular permeability, demonstrated by a diminished penetration of omalizumab‐Alexa 647 into tumor tissue. Our findings provide new evidence for a better understanding of BMP9 contribution in tumor progression and angiogenesis that may result in the development of effective targeted therapeutic interventions. Highlights: BMP9 signaling affects tumor cells, endothelial cells and pericytes in vitro. Anti‐BMP9 therapy retards tumor growth in vivo. Ex vivo analysis reveals increased vascular coverage and reduced permeability. Precursor BMP9 and pro‐domain levels are elevated in plasma of cancer patients.